IMPACTS OF ICT SECURITY TRAINING ON MALWARE CONTROL AND POLICY IMPLEMENTATION IN UNIVERSITIES' COMPUTER NETWORKS. - Oguk, Charles ' Ochieng (IJRDO -Journal of Computer Science Engineering, 2018)
The study determined the effects of ICT personnel training on malware control and security implementation within public Universities in Kenyan.  Malware infestation and unauthorized practices in information systems have been in the rise in Kenyan universities, thereby compromising integrity of critical information therein.  studies indicate that malware causes breaches of data integrity and availability.  While universities and other institutions conduct employee security training in order to lessen the impact of such information systems' security breaches, the effectiveness of such trainings with respect to security elements have not been established. The desire to assess the real effects of such training on the intended purpose has led to a focused attention in ICT security Training and its effects on malware control and implementation of  security policies within public Universities in Kenyan.  The study objectives have been; to investigate the effects of ICT personnel training on malware control ; to determine the effects of ICT personnel training on implementation of security policies in computer networks within universities in Kenya. Out of  31 public Universities in Kenya, with  a population of 409 network related personnel, a sampling formula was employed that yielded 203 personnel as a sample. Questionnaires were administered to  the sample for data collection. Data  analysis was mainly through correration and regression model in Tobin’s Q equation in  relation to Likert model. The major outcome of the study was  a positive correlation between ICT security training and all the features  of malware control and security policy.  The findings could be significant ICT managers for boosting IT security management.